Spillovers to Central America in Light of the Crisis : What a Difference a Year Makes - Swiston, Andrew (Washington, D.C. : International Monetary Fund, 2010)
This paper investigates Central America's external linkages over the last fifteen years of increased integration in light of the 2008-09 global recession. Using structural VAR models, it is found that a one percent shock to U.S. growth shifts economic activity in Central America by 0.7 to 1 percent, on average. Spillovers from global shocks and the rest of the region also affect activity in some countries. Spillovers are mostly transmitted through advanced country financial conditions and fluctuations in external demand for Central American exports. Shocks to advanced economies associated with the 2008-09 financial crisis lowered economic activity in the region by 4 to 5 percent, on average, accounting for a majority of the observed slowdown. The impact was almost twice as large as elasticities estimated on pre-crisis data would have predicted. These results underscore the importance of operating credible policy frameworks that enable a countercyclical policy response to external shocks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet